Women in call centres - Singh, Preeti; Pandey, Anu (2005)
This study looks at aspects of employment of women in call centres in India, based on a survey of 100 women employees. It examines the recent phenomenon of women working in night shifts, as well as the impact of call centre employment on women's health family life and decision-making powers. The study finds a direct and adverse effect of night shift employment on the health of women. But there is also a greater acceptance of such `non-traditional' jobs by families across a larger segment of society. - Reproduced.
Keywords: Womens employment